43.5k views
1 vote
Solve y= ax^s+c for x

2 Answers

2 votes

Answer:


\displaystyle x= \sqrt[s]{(y-c)/(a)}

Explanation:


\displaystyle y= ax^s+c

Subtract
c on both sides.


\displaystyle y-c= ax^s+c-c


\displaystyle y-c= ax^s

Divide
a on both sides.


\displaystyle (y-c)/(a) = (ax^s)/(a)


\displaystyle (y-c)/(a) = x^s

Take the root of
s on both sides.


\displaystyle \sqrt[s]{(y-c)/(a)} =\sqrt[s]{x^s}


\displaystyle \sqrt[s]{(y-c)/(a)} =x

User Fanch
by
5.2k points
4 votes

Answer:


x= \sqrt[s]{ (y - c)/(a) } \\

Explanation:


y = a {x}^(s) + c \\ y - c = a {x}^(s) \\ (y - c)/(a) = \frac{a {x}^(s) }{a} \\ (y - c)/(a) = {x}^(s) \\ \sqrt[s]{ (y - c)/(a) } = \sqrt[s]{ {x}^(s) } \\ x= \sqrt[s]{ (y - c)/(a) }

hope this helps you

User Cube
by
5.4k points